ANALYSIS OF THE STRESS-STRAIN STATE OF THE GEARING OF A GEAR PUMP IN THE ANSYS SOFTWARE PACKAGE - Mikosianchyk, Oksana; Ilina, Olha; Mnatsakanov, Rudolf; Bespalov, Sergii; Yashchuk, Olesia; Kushch, Oleksii (Problems of Friction and Wear, 2025)
The aim of the work was to evaluate the stress-strain state in the zone of tooth engagement under friction when modeling the gear engagement of a gear pump in ANSYS Workbench. It was found that with an increase in the contact Hertzian stress from 180 to 555 MPa, the depth of the zone of distribution of equivalent Mises stresses and the depth of localization of the maximum equivalent Mises stresses increased by 20% and 23%, respectively. The analysis of the tangential stress diagrams (τxy) in the cross-section of the teeth shows that in the contact zone, the tangential stresses vary in magnitude and sign. The diagrams have two extremes, and the value of the maximum stresses on the leading surface (the initial gear tooth head) is approximately 10-15% lower than the stresses on the trailing surface (the initial wheel tooth leg). High discrepancies in determining the maximum tangential stresses in the simulation model of gearing under rolling conditions with slippage according to the Belyaev formula and in modeling have been established. The calculation formulas for determining the magnitude and sign of the maximum tangential stresses in the zone of engagement of teeth with the greatest slippage are proposed, which are consistent with the results of finite element modeling.